(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
This article explores the linguistic and cultural characteristics of words borrowed from Indo-European languages into the Uzbek language. Through an analysis of etymology, phonetics, and semantic shifts, this study sheds light on the complex processes of language contact and cultural assimilation. The investigation of Indo-European loanwords enriches our understanding of the historical and sociocultural development of the Uzbek language.